Investigation of Surface Oxidation of Cast Austenitic 304 Stainless Steel at High Temperatures - Tatiana Ivanova; Michal Kořenek; Miroslav Mashlan; Martin Fryšák (Metals)
The microstructure and surface behavior of iron-based 304 stainless steel after temperature exposure was studied by Mössbauer spectroscopy, powder X-ray diffraction, scanning electron microscopy, energy dispersive analysis and positron annihilation. The tested specimens were in the form of cylinders produced by the casting process. The samples were annealed in air in the 600–1000 °C temperature range for 36 h. Under the influence of temperature, cast 304 stainless steel underwent austenitic–ferritic transformation and tended to form an oxide layer on the surface. The oxides were mainly found in the thin surface layer (0.3 μm) and consisted of Fe oxides and oxides of alloying elements (Cr and Mn) in the form of corundum, while, in the bulk region (10 μm), the phase transformation of austenite to ferrite occurred. Surface phase inhomogeneity was studied by Mössbauer spectroscopy. The method of positron annihilation was used to study defects and the effect of annealing on the formation and removal of a defect structure.